Geneza Łódzkiego Chrześcijańskiego Towarzystwa Dobroczynności - Sosnowska, Joanna (Biuletyn Historii Wychowania, 2008)
The Łódź Christian Charity Association operated in Łódź in the years 1885-1940. Its origins go back to the year 1877 and are connected with the foundation of the first charity organization in Łódź called “Support Committee for the Poor” (Pol. abbr. KWB). The aim of the Committee, whose initiators recruited mainly from the circles of affluent bourgeoisie, was broadly understood care and social assistance addressed to the impoverished city residents. Membership fees and voluntary donations constituted a primary income source of the organization, although the funds were also raised through theatrical performances, concerts, balls and funds collections. At the onset of its activity, KWB disposed of the amount of almost 15 thousand ruble, collected among the citizens o f the city, whereas the list of the poor compiled in Łódź for the first time comprised 323 persons in need of immediate help. In 1880, the members of the Committee made a decision about the construction of a shelter for the poor, the old and the invalided persons, but the absence of an appropriate legislative act regulating the activity of the organization, prevented the realization of the project. The Statute of the organization was approved of in 1884 by tsar Alexander III. This event completes an eight-year period of operation of the Support Committee for the Poor. The main directions of social, fostering and educational activity laid out by KWB, were embraced by the Łódź Christian Charity Association, whose name was agreed upon in January 1885. A principal aim and task of the organization became eradication of street beggarhood in the city and granting financial support and aid in kind to the poor residents of Christian denomination. The realization of the laid-out aims was supposed to be achieved by opening institutions with expert knowledge in which the needy might find shelter, care, medical assistance and worthy occupation.